2014
DOI: 10.11118/actaun200957020079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the growth, meatiness and fattiness in vivo in lambs of chosen breeds and crossbreeds

Abstract: The main aim of the study was the evaluation of the growth, meatiness and fattiness in vivo in lambs (n = 122) of chosen breeds (CH: Charollais and T: Texel) and crossbreeds (CH x Sf (Suffolk), CH x T, EF (East Friesiane) x CH and EF x T. Whithin the frame of this study were also evaluated the effects of sex (S), litter size (LS), age of the dams (AD) and year of the observation (YO) on aforementioned indicators. The study was carried out on the farm in Kunčice pod Ondřejníkem during the years 2004 and 2005. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Between the 100 th and the 200 th day, the growth intensity of lambs decreased, however the lambs of the breed Ch were still characterized by higher (p < 0.05) daily gains (234.50 ± 71.2 g. da y−1 ) than the lambs of the SF breed (181.50 ± 38.4 g. da y−1 ). Petr et al (2009) also observed significant (p < 0.05) differences between mean daily gains in the same sheep breeds. An interesting finding is the change of growth intensity in both breeds in the interval from 200 to 300 days of age, when the growth accelerated in the SF breed (243.40 g/day) and decreased in the Ch breed (132.30 g/day).…”
Section: The Influence Of Breed On the Growth Ability Of Lambsmentioning
confidence: 62%
“…Between the 100 th and the 200 th day, the growth intensity of lambs decreased, however the lambs of the breed Ch were still characterized by higher (p < 0.05) daily gains (234.50 ± 71.2 g. da y−1 ) than the lambs of the SF breed (181.50 ± 38.4 g. da y−1 ). Petr et al (2009) also observed significant (p < 0.05) differences between mean daily gains in the same sheep breeds. An interesting finding is the change of growth intensity in both breeds in the interval from 200 to 300 days of age, when the growth accelerated in the SF breed (243.40 g/day) and decreased in the Ch breed (132.30 g/day).…”
Section: The Influence Of Breed On the Growth Ability Of Lambsmentioning
confidence: 62%
“…The genotype had no signifi cant eff ect on most of the monitored growth parameters. In contrast, Shaker et al (2002) and Burke et al (2003) reported a signifi cant eff ect of this factor on growth while Petr et al (2009) discovered signifi cant eff ect of this factor on LW 0 and DG 0-100 only. In terms of the individual genotypes the LW 0 ranged from 3.51 to 4.19 kg, while the lowest was found out in S 100 and the highest in S 50 T 50.…”
Section: Resultsmentioning
confidence: 86%
“…Texel lambs weighed an average of 28.388 kg over the five years evaluated. Lower weight (26.95 ± 1.21 kg) was published by Petr et al (2009). In Suffolk, the weight of non-inbred lambs was significantly higher compared to inbred lambs, as was the case with Texel lambs.…”
Section: Resultsmentioning
confidence: 91%